2009
DOI: 10.1126/science.1166500
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Zippering as an On-Off Switch for SNARE-Mediated Fusion

Abstract: Membrane fusion between vesicles and target membranes involves the zippering of a four-helix bundle generated by constituent helices derived from t- and v-SNAREs found on the target and vesicular membranes. In neurons the protein complexin clamps otherwise spontaneous fusion by SNARE proteins, allowing neurotransmitters and other mediators to be secreted when and where they are needed as this clamp is released. The membrane-proximal accessory helix of complexin is necessary for clamping, but its mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
198
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(215 citation statements)
references
References 22 publications
16
198
1
Order By: Relevance
“…Cell-cell fusion assays were performed as previously described (14,24). See SI Materials and Methods for details.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell-cell fusion assays were performed as previously described (14,24). See SI Materials and Methods for details.…”
Section: Methodsmentioning
confidence: 99%
“…mutations in the Cpx accessory helix that enhance its inhibitory activity (24), have suggested a structural basis by which Cpx might regulate these dual activities (25)(26)(27). Crystallization of the Cpx-bound truncated SNARE complex revealed that the N-terminal accessory helix domain of Cpx extends away from its central helix domain at a 45°angle to form a trans interaction with a second SNARE complex, binding within the open t-SNARE pocket of the partially zippered SNAREs (trans Cpx/SNARE or zigzag array).…”
Section: Significancementioning
confidence: 99%
“…Synaptic vesicle fusion is strictly regulated by neuronal proteins such as Complexin and Synaptotagmin. Evidence suggests that these regulators may act on the half-zippered SNARE (17)(18)(19)(20). Therefore, a kinetic pause between the N-and C-terminal zipperings would be a key factor for organizing the regulation machinery.…”
mentioning
confidence: 99%
“…Although the accessory domain is required for regulating spontaneous release, mutations of this domain do not affect the activating function of Cpx compared with wild-type neurons in rescue experiments with Cpx knockdown (28,29), and it can be entirely eliminated while still maintaining the activating function of Cpx in a reconstituted system (30). The α-helical central domain (amino acid residues 49-70) binds to the SNARE complex (31,32) and is essential for all functions of Cpx in all species studied to date, including priming (16,28,29,33), inhibiting spontaneous fusion (12,19,24,25,(34)(35)(36), and activation of Ca 2+ -triggered fusion (12-14, 19, 34, 36-38).…”
mentioning
confidence: 99%
“…The C-terminal domain of worm complexin preferentially interacts with curved membranes via a membrane-binding motif (20,21). The accessory domain (amino acid residues 28-48) regulates spontaneous fusion in neurons and it suppresses Ca 2+ -independent fusion in reconstituted systems (12,14,19,(22)(23)(24)(25)(26)(27). Although the accessory domain is required for regulating spontaneous release, mutations of this domain do not affect the activating function of Cpx compared with wild-type neurons in rescue experiments with Cpx knockdown (28,29), and it can be entirely eliminated while still maintaining the activating function of Cpx in a reconstituted system (30).…”
mentioning
confidence: 99%